STRUCTURAL TRANSFORMATIONS OF THE ECONOMY AND THE CONCEPT OF SUSTAINABLE DEVELOPMENT: INTERCONNECTION AND INTERACTION (Development Service Industry Management, 2024)
The economy's structure is the main criterion for determining a society's economic development stage. During the research, it was determined that from a general scientific point of view, the structure has the features of a stable, internally balanced object, which is characterized by cause-and-effect relationships that combine the parts of the object into structural and functional integrity; internal mechanisms; integral orientation of the system. From the standpoint of economic science, the economy's structure is understood as the ratio of the elements of the economic system, which reflects the proportions of the national economy and the state of the social division of labor. Structural changes caused by the industrial, scientific, and technological revolutions marked the transition from the pre-industrial to the industrial and later to the post-industrial stage of society's development. However, scientific and technical progress has positively impacted the development of production, raising incomes, and society's standard of living. However, at the same time, it has hurt ecology. Awareness of environmental threats and the fourth scientific and technological revolution formed a new cultural matrix of post-industrial civilization. There has been a gradual change in the value orientation of society since the formation of the concept of sustainable development. We investigated the existence of a relationship between structural changes in the economy that preceded the formation and spread of the concept of sustainable development in post-industrial society. The theoretical and practical developments of foreign and domestic scientists were studied to determine such a relationship. The reasons for the formation of the concept of sustainable development are studied, and the role of the theory and practice of social development, which is based on structural changes in the economy, is determined. Analysis and systematization of the stages of formation and implementation of the sustainable development strategy, as well as its principles and tools for achieving the set goals, was carried out.
Keywords: transformations; sustainable development; national economy; social development; economic system; cultural matrix; post-industrial society